Halal and Haram in The Clothing Industry - Siti Nur Mahmudah; Mohammad Ridwan; Husna Ni'matul Ulya (Institut Agama Islam Negeri Ponorogo, 2022)
The development of the industry is entering a new phase, namely the development of the halal industry, one of which is the halal clothing industry. According to the Global Islamic Economy Report 2017/2018, with the largest Muslim-majority population in the world, Indonesia is still inferior to neighboring countries such as Malaysia, which has started to develop the halal clothing industry. So an indicator of halal clothing is needed to compete with the country and stay on the halal path. This research uses data from a literature study which is then analyzed by analytical descriptive analysis. The results of this study found indicators that regulate halal clothing, namely: a) ensuring that the raw materials used are halal raw materials, b) the production process should not be mixed with haram goods, c) after the production process is complete if there is a product storage period must be stored in a separate place with goods that are haram or unclean, d) the distribution of production must be based on the principles of benefit and justice.